Amostragem seqüential (presença-ausência) para Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) na cultura do milho - Farias, Paulo R. S.; Barbosa, José C. [UNESP]; Busoli, Antônio C. [UNESP] (Springer Nature, 2001)
The sequential sampling of insect pests (presence-absence) has become important in the last years, specially when the insects are difficult to be quantified. To solve this problem in relation to Spodoptera frugiperda (J. E. Smith), a sequential sampling plan was developed. The sample unit was evaluated considering the presence or absence of the insect, independently of its total number. The experiment was conducted in Jaboticabal, São Paulo State, Brazil, in three fields of 0.5 ha divided in 100 plots of 50 m2 (5 × 10 m). Each plot was identified with a number from 1 to 100. A threshold level of 20% was assumed to set the sampling plan. The analyzed data allowed two lines to be generated: the superior one, representing the condition in chemical control is recommended (S1=1.7095+0.1452N); and the inferior one, when chemical control is not recommended (S0=-1.7095+0.1452N). The sequential sampling was efficient to indicate if control of S. frugiperda on corn crop was necessary or not.
Sequential sampling (presence-absence) to Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) on corn crop
Keywords: Fall armyworm; Insecta; Sampling plan; Zea mays